Demonstrating a Technology-Mediated Intervention to Support Medication Adherence in Community-Dwelling Older Adults in Primary Care: A Feasibility Study. (May 2019) - Siu, Henry Yu-Hin; Delleman, Bethany; Langevin, Jessica; Mangin, Dee; Howard, Michelle; Fang, Qiyin; Price, David; Chan, David
Background: Medication non-adherence can lead to significant morbidity and mortality. This 4-week feasibility study aims to demonstrate that the eDosette intervention can be implemented with older adults in primary care.Method: Fifty-six older adults from four primary care sites in Southwestern Ontario, Canada participated. The intervention involved generating, for pharmacist review, weekly medication administration records based on transmitted data captured by the eDosette. The primary outcome is implementation feasibility defined by recruitment, adherence rates, frequency of captured missed and late doses, descriptions of clinical work resulting from the intervention, and participant feedback.Results: The recruitment rate was 24% (57/240); one withdrew due to personal reasons. The mean observed adherence rate was 82% (range 49%-100%). Overall, participants missed 505 and took 2, 105 doses late; 118 clinical decisions occurred with 72 unique medication changes in 31 participants. Participants found the eDosette easy to use and did not feel that they were viewed negatively because of their potential non-adherence.Conclusion: The eDosette intervention could be feasibly implemented in primary care with older adults. Providing information about when an older adult takes their medications could play a role in medication adherence by prompting more informed discussions between the older adult and primary care clinicians.